Edukasi PHBS Dan Kecacingan Pada Keluarga Penderita Stanting Kelurahan Banta-Bantaeng Kecamatan Rappocini Kota Makassar - Sulasmi; Nur Haidah; Juherah (Universitas Mataram, 2024)
Stunting is a chronic nutritional problem caused by a long-termlack of nutritional intake, which interferes with a child's growth. The causesof stunting in children vary, ranging from economic problems, education,inadequate nutritional intake, sanitation problems, genetic factors to a lackof clean and healthy living behavior practices and poor sanitation, all ofwhich contribute to the risk of stunting. The priority problem for communityservice locations is that Stunting families lack knowledge about clean andhealthy living behavior (PHBS). Based on the Ministry of Health's SSGI, theprevalence of stunting in South Sulawesi will reach 27.2% in 2022, placingthis province in 10th place for the highest prevalence of stunting in Indonesia.Makassar City is an area with a risk of stunting, especially in Banta-BantaengVillage. The targets of this service are mothers from growing families inBanta-Bataeng Village, Makassar City. The methods used includecounseling about stunting, worm diseases and PHBS training. To shapechildren to have the ability and independence to prevent disease, improvetheir health, and play an active role in the environment where they live.Thetarget for understanding the implementation of counseling is 85%. Theresults of counseling related to PHBS education increased understanding by62.8% increased to 88.5%, counseling related to worm disease increasedunderstanding by 65.8% increased to 88.5%, and counseling related toPHBS, there was an increase of 74.2%, increasing to 91.4%. So, it wasconcluded that PHBS and worm education in families suffering fromstunting, Banta-Bantaengm Village, Rappocini District through counselingand training methods was known to be able to increase knowledge